2021
DOI: 10.1159/000518013
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Combined Hamartoma of the Retina and Retinal Pigment Epithelium

Abstract: There is no consensus on whether and when surgical treatment is indicated for combined hamartoma of the retina and retinal pigment epithelium (CHRRPE). We aim to discuss the benefits of surgical intervention and techniques that may improve the outcome. A 24-year-old man experienced progressive visual loss for 6 months in his left eye due to CHRRPE. At presentation, visual acuity was 1.3 LogMAR and fundoscopy revealed extensive tractional pre- and epiretinal membranes, subretinal exudation, and a vasoproliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A total of 13 small case reports (43 patients) have shown that surgery results shows good visual outcomes (success rate >70%). 17 , 18 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 It was found that 39 of the 43 patients (90.7%) had postoperatively improved in VA. Because of rarity of the disease the largest cohort study was published by Sun et al. 30 in 2020 with only 15 patients.…”
Section: Surgical Management Of Epiretinal Membranementioning
confidence: 96%
See 1 more Smart Citation
“…A total of 13 small case reports (43 patients) have shown that surgery results shows good visual outcomes (success rate >70%). 17 , 18 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 It was found that 39 of the 43 patients (90.7%) had postoperatively improved in VA. Because of rarity of the disease the largest cohort study was published by Sun et al. 30 in 2020 with only 15 patients.…”
Section: Surgical Management Of Epiretinal Membranementioning
confidence: 96%
“…Because of the publication of these small case studies, including improved fluidics control, small-gauge instruments, better internal light sources, and the development of new dyes, that surgical outcomes can be improved and complications reduced. 31 …”
Section: Surgical Management Of Epiretinal Membranementioning
confidence: 99%